(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Good customer service involves providing courteous and quick service to meet customers’ needs during their dining experience. Restaurant owners can encourage this kind of good service by honoring employees who are exceptionally gifted in this area and having them train others. Customers who can see managers, supervisors, and waiter staff are more likely to give employees the opportunity to provide good customer service by making requests. Being visible also helps customers feel they are having a better experience by showing that they are right there to help. This reveals that the handling technique employed by Giligans is a quick response to the customer. Engaging in active listening in order to make that person feel truly heard, understood, and served and to give great customer service to the restaurant server needs to be able to listen to what the customer wants. Some issues encountered by the respondents were wrong orders, spilled glasses of water, problems with the food, encountering rude customers, and children running when served. It was handled by management by apologizing to the guest for the wrong order, giving a genuine apology, taking the food and feedback to the kitchen, responding with an apology and a solution, and last talk to the parents of the children to avoid running. Employees should maintain their quick responses and listen actively to acquire information. Employees should always be ready for unexpected situations and ready to give solutions. Employers must have strategies for boosting employees’ confidence and morale and allowing the employees to personalize their own space. In terms of children running when you serve, employees should talk to the parents of children to avoid accidents that may be caused.